Youtube as an alternative to learning media: a case study - Mochamad Cholik; Susi Tri Umaroh; Tri Rijanto; Soeryanto Soeryanto (Faculty of Engineering, Universitas Negeri Yogyakarta, 2023)
21st century-era learning is undergoing significant changes. The learning process is carried out with a combination of various digital media that can be accessed easily by students and teachers in learning. Based on the covid-19 pandemic, it is also an effort to follow the development of technology and information. Vocational students in the Field of Automotive Engineering Expertise must have competence in maintenance and repair in vehicles. Therefore, with learning that still cannot be face-to-face in full, they must utilize technology and information to support learning and understand theoretical and practical materials. This research aims to find out the level of use of YouTube as a medium to support the learning of vocational students in the field of automotive engineering expertise. The sample taken in this study was a student of SMK Senopati Sidoarjo East Java Indonesia. They are majoring in Light Vehicle Engineering and Motorcycle Business Engineering. This study shows that YouTube is beneficial for students to support online learning in the pandemic period and overcome problems in the automotive field. There are tutorial videos that are very easy to access to help students overcome the pain in their vehicles and understand learning materials.